Análisis de la movilidad en Zaragoza y su influencia en la construcción de los cinturones de circunvalación - Garrido Palacios, José (Geographicalia, 2017)
This work analyses the mobility in the town of Zaragoza and the more important aspects: the motorization, modes of travel, distribution of time and the trip purpose, such as the flow of traffic in the futuring road network.